PENANGGULANGAN PERDAGANGAN ORANG OLEH BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA KABUPATEN SAMBAS - E.01107066, Nurfazila (FISIP Universitas Tanjungpura, 2013)
Writing journals are meant to learn handling of the implementation of the trade that have been implemented by theWomen Empowerment and Family Planning Sambas District and to find out the factors supporting factor sand obstacles fort he handling of the trade. Insider trading is a phenomenon of modernens lavement in Indonesia, it is the third largest crime after illegal drugs and arms trade. Therefore, this topic belongs interesting to examined, type in this research study is the evaluation study with qualitative approach. Research findings are to be supporting factors: (1). Sambas Regent Decree No.103 of Â 2011, (2). Stop home in Malaysia and Indonesia's national borders, (3). Economic existence of the woman or group. Factor blockers: (1). Difficulties in reaching out tothe community as far from the urban district, (2) the condition Â of the damaged roads, (3). Community education level sare low, (4). Lack of sufficient funds. Handling of implementation,(1).Cross-sectoral collaboration,(2).Socialization.Keywords:Countermeasurestrading, executionhandling ofinsider trading, the phenomenon of modernbondage